Low impedance characterisation and modeling of high power LDMOS devices - Malan, Pieter Jacob De Villiers (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2005.